DEVELOPMENT OF A WEB APPLICATION FOR AN ONLINE BOOKSTORE (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This application helps to regulate the activities of bookstores with comprehensive functions, to satisfy customer needs, to make quick and easy decisions, to save time, and to grow the business.